Primary vaginal leiomyosarcoma: A case report emphasizing multidisciplinary care of a rare entity - Fadoua Jebrouni; Hanan Bailal; Mouhsine Omari; Kaouthar Khater; Asmae Bali; Ouissam Al Jarroudi; Sami Aziz Brahmi; Said Afqir (Radiology Case Reports, 2025)
Leiomyosarcoma (LMS) is a rare malignant tumor derived from smooth muscle cells. It usually occurs in the uterine cavity, other localizations, such as vaginal leiomyosarcoma, are atypical. Due to the nonspecific nature of its clinical presentation, vaginal LMS may be misdiagnosed as a benign gynecological neoplasm and is often detected at an advanced stage. Here we report a case of a 45-year-old patient who was diagnosed with metastatic vaginal LMS at the regional oncology center of Oujda in Morocco. Following the multidisciplinary team meeting discussion, the patient received first-line doxorubicin-based chemotherapy. Due to the progression of the disease in the lungs, the patient received second- line ifosfamide-based treatment, with an excellent tolerance. Based on our case and a review of the literature, the vaginal localization of leiomyosarcoma remains exceptional. Diagnosis is essentially based on histology, and immunohistochemical complementation is always necessary to rule out other diagnoses. The disease's nonspecific symptoms often delay diagnosis. Treatment must be individualized and should always be discussed in a multidisciplinary meeting. In localized stages, the mainstay of treatment is surgery, combined with chemotherapy and radiotherapy. In advanced stages, treatment is mainly based on chemotherapy. Targeted therapies and immunotherapy are under investigation as promising treatments for leiomyosarcoma. This case report enriches the limited data on vaginal leiomyosarcoma. Vaginal presentation of leiomyosarcoma remains uncommon. Due to the nonspecific symptoms of the disease, diagnosis is often delayed. This leads to a worse prognosis. The rarity of leiomyosarcoma also makes it difficult to treat, as no standard treatment protocol exists.